The Horn of Africa - Henze, Paul B. author. aut Link
II, 278 p.
Keywords: There are many books on individual countries of the Horn, but this one is unique in treating the region as a whole, stressing interactions among as well as within Sudan, Ethiopia and Somalia and, in turn, their relations with neighbouring regions of Africa and the Middle East. The author summarizes the history of the region from earliest times to the 19th century and then concentrates on Russian and American involvements.